2009
DOI: 10.1109/tit.2009.2027484
|View full text |Cite
|
Sign up to set email alerts
|

Communication Under Strong Asynchronism

Abstract: We consider asynchronous communication over point-to-point discrete memoryless channels without feedback. The transmitter starts sending one block codeword at an instant that is uniformly distributed within a certain time period, which represents the level of asynchronism. The receiver, by means of a sequential decoder, must isolate the message without knowing when the codeword transmission starts but being cognizant of the asynchronism level. We are interested in how quickly can the receiver isolate the sent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
109
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 53 publications
(110 citation statements)
references
References 18 publications
1
109
0
Order By: Relevance
“…With such modifications, one defines the capacityC(A) in exactly the same manner as C(A); the key results of [1], [2] provide upper and lower bounds onC(A) (but notC ǫ (A)). The definition (6) was chosen, perhaps, to model the situation when one wants to assess the minimal number of channel uses (per data bit) that the channel remains under the scrutiny of the decoder, whereas our definition…”
Section: Problem Formulation and Notationmentioning
confidence: 99%
See 4 more Smart Citations
“…With such modifications, one defines the capacityC(A) in exactly the same manner as C(A); the key results of [1], [2] provide upper and lower bounds onC(A) (but notC ǫ (A)). The definition (6) was chosen, perhaps, to model the situation when one wants to assess the minimal number of channel uses (per data bit) that the channel remains under the scrutiny of the decoder, whereas our definition…”
Section: Problem Formulation and Notationmentioning
confidence: 99%
“…Recently, motivated in part by the sensor networks in which nodes exchange data very infrequently (thus, making constant channel-tracking impractical), Tchamkerten et al [1] formulated the problem in an elegant way and later demonstrated [2] that there are indeed significant advantages in going beyond the conventional synchronization approach.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations